PELAKSANAAN EVALUASI LAYANAN BIMBINGAN KONSELING - Riswani Riswani (An-Nida', 2011)
The aim of this research is to know how the does the implementation of the evaluation of guidance and counseling service and also what are the factors influence its in District Of Rengat Indragiri Hulu. Population in this research is all school counselors exist in senior high school at Rengat regency. The Senior High School are SMUN I, SMUN II and some SMU private sectors. She uses purposive sampling in taking the sample because the implementation of the guidance and counseling service in private senior high school less optimal. Therefore, the researcher takes only the school counselors in the senior high schools which are optimal in implementation of guidance and counseling service, those are SMUN I SMUN II Rengat. Data collected by interview and observation and analyzed by descriptive qualitative technique. The research finds that the implementation of guidance and counseling service was less maximal. The factors influencing this service were school counselor, instrument of evaluation, and time. Research also suggested that headmaster can budget fund and provided facilities which needed to evaluate the guidance and counseling service. Counselor teacher had to do her/his work as a school counselor like, planning, evaluation, follow-up and analysis of guidance and counseling service at school